Semantics - Kearns, Kate (Palgrave Macmillan, 2011)
This introductory textbook assumes no prior knowledge and covers a wide range of core topics in formal semantics. Now thoroughly updated, the second edition features new chapters on semantic composition, type theory and the lambda calculus, as well as a revised discussion of Pragmatics and a variety of new exercises